Experimental investigation of leakage-induced pipe erosion outside of pipe leaks - Pike, Stefan (Department of Civil Engineering, 2016)
The problem of water loss from water distribution systems is an issue that faces municipalities worldwide. A large proportion of water loss is a result of leakage. With increasing water scarcity across the globe, it is imperative to conserve water resources, and hence reduce leakage in water distribution systems as best we can. Leaks develop in various different forms, and they form in pipes of all materials. It has been observed in numerous cases around the world that pipe material has been removed from the pipe surfaces adjacent to leaks in excavated failed water distribution pipe specimens. It was proposed by various researchers that this pipe material was being removed as a result of abrasive soil action caused by the pipe leak itself. When pressurised water distribution pipes fail, they emit high velocity jets of water into the surrounding soil bed. Research has shown that high velocity jets of water entering a granular soil bed have the ability to fluidise the bed, allowing the granular particles to move freely. This fluidisation mechanism is known as internal fluidisation. The concept of internal fluidisation offers an explanation for the erosion of pipe material adjacent to pipe leaks. In this study, the removal of pipe material adjacent to leaks due to internal fluidisation has been termed "leakage-induced pipe erosion." This phenomenon has received minimal attention from researchers in the past. Leakage-induced pipe erosion has the potential to aggravate small existing leaks. There are two main implications of aggravating small leaks; firstly, where water authorities do not utilise active leak detection programmes, aggravating the initial leak conditions of small leaks can result in increased long term water losses. Secondly, in water distribution systems where the water authority does implement active leak detection programmes, aggravating small leaks increases the probability of finding and repairing them. This aim of this study was to experimentally investigate the influence of various factors on the leakage-induced erosion process. Five main factors were investigated, namely bedding material grain size, cover depth, leakage flow rate, initial leak orientation and pipe material. An experimental setup was designed and manufactured in order to provide a controlled environment in which to investigate the factors affecting leakage-induced pipe erosion.